Repeatability of land time-lapse seismic surveys - Otway project 2D test line case study - Pevzner, Roman; Shulakova, V; Kepic, Anton; Al-Jabri, Yousuf; Urosevic, Milovan (EAGE, 2009)
Full range of 2D and 3D borehole and surface seismic methods are utilised for time-lapse surveys for monitoring of CO2 sequestration at Otway Basin pilot project site. Conducting land time-lapse surveys is challenging task because of typical variability of ground conditions, source-receiver coupling, ambient noise which results in poor repeatability of land seismic data. We analysed the major factors influencing repeatability of land seismic data. We also analysed both synthetic and field data for possible limitations of the surface reflection seismic method when it comes to repeatability. We show that changes in near surface conditions will produce kinematic differences but also different ground roll patterns. This will in general require slightly different parameters for processing of two successive surveys if they are acquired for vastly different soil conditions. We then conduct extensive numerical and field tests to show that the S/N variability as function of the source strength relative to the background noise level is crucial. Source type is less important for time lapse surveys as long as S/N ratio is high. Our tests included impact (weight drop) and vibrating (IVI Mini-Buggy) sources.